2020
DOI: 10.1177/2396987320932069
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intracerebral haemorrhage – Results from a prospective population-based study

Abstract: Introduction While the relationship between hypertension and incident intracerebral haemorrhage is well established, other risk factors are less clear. This study examined risk factors for primary intracerebral haemorrhage, separately for lobar and non-lobar intracerebral haemorrhage. Patients and methods Incidence of intracerebral haemorrhage was studied among 28,416 individuals from the population-based Malmö Diet and Cancer cohort. Intracerebral haemorrhage cases were ascertained using the Swedish Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Apolipoprotein E (APOE)containing lipoproteins, such as high-density lipoproteins, mediate the inhibition of platelet function [13]. Recent publications also showed that apolipoproteins were related to hemorrhage [14,15]. However, no studies have been conducted on the effect of these gene polymorphisms on bleeding complications during DOAC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Apolipoprotein E (APOE)containing lipoproteins, such as high-density lipoproteins, mediate the inhibition of platelet function [13]. Recent publications also showed that apolipoproteins were related to hemorrhage [14,15]. However, no studies have been conducted on the effect of these gene polymorphisms on bleeding complications during DOAC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was consistent with the results from a prospective population-based study in 2020, which showed that higher ApoB levels were significantly associated with a lower risk of ICH after multivariable adjustment (per 10-mg/dl increase, HR 0.94, 95% CI 0.90-0.99). 28 In addition, a report from the China Kadoorie Biobank involving approximately 5,000 ICH cases also showed inverse relationships between ApoB and ICH (RR 0.86, 95CI, 0.83-0.90), and between LDL-C and ICH (RR 0.86, 95% CI 0.80-0.92), 29 and the level of ApoB was confirmed to be closely related to the LDL levels. 29 However, in their MR study, only LDL-C was included as exposure, whereas ApoB was not considered, and a nonsignificant causal relationship was observed.…”
Section: Discussionmentioning
confidence: 94%
“…For patients with higher risk, it is recommended that the low-density lipoprotein should be reduced to less than 1.4, and too low cholesterol level and triglyceride will increase the risk of bleeding [23]. Relevant literature has mentioned that the reduction of ApoB or LDL-C is signi cantly correlated with the risk of cerebral hemorrhage [24][25][26]. On the other hand, statins themselves can directly interfere with the coagulation system and platelet activation [27].…”
Section: Discussionmentioning
confidence: 99%